KARAKTERISTIK TAFSIR FI ZHILAL AL-QUR'AN - Zaidi Muhammad (Al Muhafidz: Jurnal Ilmu Al-Qur'an dan Tafsir, 2021)
Abstrac Tafsir fi Zhilal Quran was written in the range of 1952 to 1965. He had time to revise the first thirteen juz of his interpretation during his long detention1. This interpretation led Sayid Qutub to explore the various moral messages of Islam that were conveyed through Muhammad's treatises, which strengthened faith and could provide a perfect ideological foundation. It was so phenomenal that Sayid Qutub wrote a fi dzilal al-quran interpretation, with its unique methods and characteristics, rich in literary and social language in his dakwa, inviting and inviting in a beautiful language style.Sayid qutub can complete his Tafsir in prison with enthusiasm and enthusiasm in writing his tafsir, with the aspiration to provide the best legacy for future generatio Abstrak Tafsir fi Zhilal Quran ditulis dalam rentang antara tahun 1952 sampai tahun 1965. Beliau sempat merivisi ketiga belas juz pertama tafsirnya semasa penahanannya yang panjang.1 Tafsir ini membawa Sayid Qutub menjelajahi berbagai pesan moral Islam yang diemban melalui risalah Muhammad Saw, menguatkan Iman dan dapat menjadikan fondasi ideologi yang sempurna. Begitu fenomenalnya Sayid Qutub menulis tafsir fi dzilal al-quran, dengan metode dan karakteristiknya yang khas kaya akan bahasa satra dan social dalam dakwanya, menyeru dan mengajak dengan gaya bahasa yang indah. Sayid qutub dapat menyelesaikan Tafsirnya dalam penjara dengan antusias dan semangat dalam menulis karya tafsirnya, dengan cita-cita untuk memberikan waritsan yang terbaik untuk generasi yang akan datang. 1 Muhammad Zhirzin, Jihad menurut Sayid Qutub, (Solo, Ira Intermedia, 2001) h.134